Pre-impregnated natural fibre-thermoplastic composite tape manufacture using a novel process. (October 2017) - McGregor, O.P.L.; Duhovic, M.; Somashekar, A.A.; Bhattacharyya, D.
Abstract: Pre-impregnated flax and thermoplastic poly(amide) composite tapes have been produced using a novel process. The manufacturing method uses an impregnation unit with a siphon system to impregnate continuous flax yarns with the polymer in the form of a slurry. After water evaporation, the powder is sintered and the coated yarns are compressed by passing them through a pair of heated rollers. Using a parametric study of the process, tape quality has been assured using the key outcome criteria of tensile strength/stiffness, surface roughness, fibre weight fraction, width and thickness. The temperature of the air heater placed before the roller has the biggest influence on tape quality. A heating model was developed using finite element software LS-DYNA. The research novelty comes from producing composite tapes with good tensile properties and surface finish using aligned natural fibres; the feasibility of automated tape placement and winding has also been demonstrated.